Globalização e políticas públicas: vida, paixão e morte do Estado nacional? - Moraes, Reginaldo Carmello Corrêa De [UNESP] (Centro de Estudos Educação e Sociedade - Cedes, 2004)
Confronting arguments selected in the literature, this paper seeks to give the reader a synthetic vision of the constitution of the organized capitalism (1870-1970), its identity crisis (1970s) and the emergence of a capitalism reorganized through the process we call globalization. A special emphasis is given to the economic globalization in its three reciprocally conditioned dimensions (trade, production, finance). The text also highlights the role of the national State, in these three moments, as an arena under discussion and a relevant political actor.

Confrontando argumentos apresentados em literatura selecionada, o artigo visa a dar ao leitor uma visão sintética de constituição do capitalismo organizado (1870-1970), de sua crise de identidade (na década de 1970) e da emergência do capitalismo re-organizado pelo processo que se tem chamado de globalização. Destaque especial dá-se à globalização econômica nas suas três dimensões reciprocamente condicionadas (comércio, produção, finanças). Também se destaca o papel, nesses três momentos, do Estado nacional, como arena em disputa e como ator político relevante.
Globalization and public policies: life, passion and death of the national State?
Keywords: globalization; Neo-liberalism; Interventionism; National State; Market; Globalização; Neoliberalismo; Intervencionismo; Estado nacional; Mercado